Artificial Intelligence in International Trade: A Bibliometric Analysis - Mihaela Gabriela Belu (Romanian Economic Journal)
Artificial intelligence (AI) has emerged as a key force reshaping the international business landscape. Artificial intelligence, known as one of the disruptive technologies of the moment, will produce important changes in the mechanism of unfolding specific to foreign trade operations. The research is based on a quantitative research method, bibliometric analysis. By querying the existing database on the Scopus platform, scientific papers (research articles, books, papers presented at conferences) containing the keywords in the title, abstract or keywords of the documents were identified. The bibliometric analysis carried out can be a guide for future research directions and for identifying strategic directions for the implementation of AI in international trade. The results obtained can also guide market participants, especially international trade companies, on how artificial intelligence could be used in the process of conducting export-import business. At the same time, the results can help academic researchers explore issues related to the application of artificial intelligence in international trade in future studies.